Food Safety and Halal Issues in Food Aggregator Applications: “A Consumer's Point of View” - Khairunisa Ramadhani (ITB AAS INDONESIA Surakarta, 2022)
Food delivery services are developing significantly, especially during the COVID-19 pandemic. Food aggregator application is one of the online systems which enables customers to order delivery food from several food providers. This application was made as a simple app to make it easy to use by customers. In addition, it also makes it easier for food producers to sell their products. However, it has its limitation in which the consumers do not know the safety and halal status of the products offered in this application. This research aimed to understand the consumers' perceptions of the food's safety and halal status in this food delivery system. This descriptive-qualitative research was held in January - February in DIY through in-depth interviews using an online meeting platform. The results showed that the consumers believe that the products sold in the aggregator application are safe and halal. The consumer's choice and trust depended on the restaurant's rating, products' photos, and their taste. In the product's safety context, the consumers justified the product quality from its packaging. As for the halal label of the product, the consumers believe that the product is halal if there is no information that these products contain non-halal ingredients